Longitudinal analysis methodologies to determine profiles of informal workers from Gran Córdoba - Iglesias, Maximiliano (2019)
Fil: Iglesias, Maximiliano. Universidad Nacional de Córdoba. Facultad de Ciencias Económicas; Argentina.